2022
DOI: 10.3390/cimb44060172
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Ameliorates Cardiac and Hepatic Toxicity Induced by Azithromycin-Etoricoxib Drug Interaction

Abstract: The complexity of prescribing safe and effective drug therapy is still challenging. Due to the increased number of medications taken by patients, the potential for drug-drug interactions has clinically important consequences. This study focuses on the potential drug-drug interaction between azithromycin and etoricoxib and the possibility of counteracting this adverse reaction by giving ascorbic acid intraperitoneally to male albino rats. Sixty adult male albino rats weighing 150–180 g were used. The rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
3
2
0
Order By: Relevance
“…The co-treatments of ATZ-exposed rats with zinc oxide nanoparticles or ascorbic acid in our study modulated the alteration in ALT and AST enzymes and come in line with Mahmoud et al [ 54 ] and Hamza et al [ 83 ], respectively, which also restored the normal levels of total proteins and albumin as in agreement with Hassan et al [ 84 ] and Abou-Kassem et al [ 85 ], respectively, indicating their cytoprotective and antioxidant qualities. Previous studies have shown that vitamin C ameliorated the elevated serum ALT and AST activities in rat models of malathion hepatotoxicity [ 86 ] and organophosphate pesticide toxicity [ 87 ].…”
Section: Discussionsupporting
confidence: 91%
“…The co-treatments of ATZ-exposed rats with zinc oxide nanoparticles or ascorbic acid in our study modulated the alteration in ALT and AST enzymes and come in line with Mahmoud et al [ 54 ] and Hamza et al [ 83 ], respectively, which also restored the normal levels of total proteins and albumin as in agreement with Hassan et al [ 84 ] and Abou-Kassem et al [ 85 ], respectively, indicating their cytoprotective and antioxidant qualities. Previous studies have shown that vitamin C ameliorated the elevated serum ALT and AST activities in rat models of malathion hepatotoxicity [ 86 ] and organophosphate pesticide toxicity [ 87 ].…”
Section: Discussionsupporting
confidence: 91%
“…Hamza et al . [ 53 ] reported findings similar to these. Higher Az doses were linked to nephrotoxicity and reduced renal function [ 54 ].…”
Section: Discussionsupporting
confidence: 74%
“…Az1 exhibited significant caspase-3 immunoreactivity in hepatocytes and bile ductal epithelium. Hamza et al [53] reported findings similar to these. Higher Az doses were linked to nephrotoxicity and reduced renal function [54].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Various drugs have been withdrawn from the drug market due to serious DDIs, which include mibefradil, terfenadine, and cerivastatin. Hamza et al [ 10 ] evaluated the DDIs between etoricoxib and azithromycin and administered ascorbic acid intraperitoneally to male rats in order to identify any adverse reactions resulting from the treatment. The authors demonstrated that ascorbic acid had significant hepatic, antioxidant, and cardiac ameliorative effects and can alleviate drug interaction toxicity.…”
mentioning
confidence: 99%